Curiosity and self-concept of school adjustment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Doyle, Michael Dennis (Massey University, 1974)
This study, as a piece of descriptive research, is an extension of a similar one done by Maw and Maw (1970) concerning the relationship between curiosity and the self-concept. Whereas they hypothesised that children high in curiosity are also those who have successfully interacted with their environments, the general hypothesis for this study was that children who have positive self-concepts of themselves in the school environment will also be ones who exhibit curiosity in that situation. This hypothesis was formulated as a consequence of the writer's adherence to a theory of active intelligence, and view of self-concept as a highly task-specific construct. Measures of curiosity, global self-concept, and self-concept of school adjustment were taken. In general terms curiosity was defined as a preferred cognitive strategy which is utilized to cope with challenging stimuli and manifested in the way in which the individual is predisposed to achieve and resolve conceptual conflicts. Global self-concept was defined as an individual's perception of his innate capacity to cope effectively with his environment. Similarly self-concept of school adjustment was defined as a student's perception of his innate capacity to cope effectively in the specific environment of the classroom. Each of these three variables was operationally defined in terms of the instruments used to measure them. Where possible, the same instruments as used by Maw and Maw in their study were used in this research. No new instruments were constructed for this study. Measures of curiosity were taken from Maw and Maw: (1) Teacher's Rating Scale of Curiosity, (2) Self-appraisal of curiosity, (3) The Which to Discuss Test. Measures of global self-concept were obtained from the following instruments: (1) Parts of the California Test of Personality (C.T.P.), (2) Parts of the Children's Personality Questionnaire (C.P.Q.). A measure of self-concept of school adjustment was obtained from subjects recorded responses to factor 2 E : School Relations, of the California Test of Personality (C.T.P.) and from the tester's recorded observation on the Bristol Social Adjustment Scale: factor U (Unforthcomingess). P.A.T. results for reading comprehension and maths were taken from school records. The subjects were 20 children from the senior room of a local two-teacher school. There were ten boys and ten girls. It is felt that they are representative of New Zealand rural children. Administration and scoring of the tests was done by the writer, who at the time of testing was also the children's teacher. The results of the study did not support the general hypothesis, and only partly supported Maw and Maw's (1970) findings. However, some relationship between the variables curiosity, self-concept and self-concept of school adjustment was shown to exist. Also a highly significant relationship was recorded between curiosity and school achievement. A lack of significant relationship recorded between the teacher's rating of curiosity and the C.T.P. measure of Total Personal Adjustment was taken to suggest that either the tests in fact measure different things than curiosity and personal adjustment or, that there was error in administration or scoring of at least one of the tests. Both of these factors, as measured on the same tests, correlated significantly in the Maw and Maw study. Unfortunately the lack of correlation mentioned above also affected the recorded relationship between the teacher's rating and the school adjustment measure from the C.T.P. One implication of these results is that curiosity as a task-specific concept is merely one aspect of cognition. The possibility of marker bias was discussed, but if this can be discounted then the significant correlations which existed between curiosity, school adjustment and school performance can all be taken as evidence that curiosity is in fact connected with intelligence. Consequently, it would seem that better school adjustment is more readily found in higher achievers.
Keywords: Child psychology; Curiosity